(untitled) (Belmont, CA, 2006)
This is a very good textbook for an introductory course in educational research methods. I actually prefer the chapter order better than in some others I’ve looked at and used. I like proceeding from designs strongest in internal validity and confidence in causality to those weakest in these characteristics. And treating statistics up front provides students the tools to better understand the complexities and nuances of different research methods
Keywords: Education; Research